Assessing deficit irrigation strategies for corn using simulation - Kisekka, Isaya; Aguilar, Jonathan P.; Rogers, Danny H.; Holman, Johnathon; O'Brien, Daniel M.; Klocke, N. (My University, 2016)
Declining groundwater levels in the Ogallala aquifer due to withdrawals exceeding annual recharge result in diminished well capacities that eventually become incapable of meeting full crop water needs. Producers need recommendations for deficit irrigation strategies that can maximize net returns in most years under low well capacities. The objectives of this study were to (1) calibrate and validate the CERES-Maize model in DSSAT-CSM v4.6 under southwest Kansas soils and climatic conditions and (2) apply the calibrated model to assess three factors related to irrigation management: (i) the optimum plant-available water threshold to initiate irrigation for maximizing net returns, (ii) the effect of percentage soil water depletion at planting on yield, seasonal transpiration, water productivity, extractable soil water at maturity, and net returns, and (iii) the effect of late irrigation season termination on extractable soil water at physiological maturity, yield, and net returns. The CERES-Maize model in DSSAT-CSM v4.6 in conjunction with short-term experimental data and 63 years (1950 to 2013) of historical weather data were used in this study. The calibrated model was able to predict end of season grain yield with acceptable accuracy (NSE > 0.9, 0.13 < %RMSE < 0.19), indicating that the model could be used for assessing alternative management strategies for optimizing the use of limited water for irrigating corn in southwest Kansas. Irrigation scheduling based on a 50% plant-available water threshold maximized net returns compared to initiating irrigation at greater soil water content at corn prices ranging from $0.10 to $0.26 kg-1. Accounting for inter-annual variations in weather and irrigation downtime due to repairs, 14 to 17 irrigation applications of 25 mm of water each would be needed to maintain soil water at 50% of plant-available water during the season. Having soil water in the top 1.2 m of the soil profile between 0% and 25% depleted at planting maximized net returns, although it also resulted in more extractable soil water at physiological maturity. Terminating irrigation 90 or 95 days after planting depending on corn price maximized net returns and resulted in the lowest amount of extractable soil water at physiological maturity, implying that opportunities exist to mine stored soil water toward the end of the season even under deficit irrigation. We recommend that late season irrigation termination be done in conjunction with soil water monitoring and management- allowable depletion techniques to minimize potential reduction in yields. Before adopting any of the management strategies assessed in this study, producers should consider the unique yield potential constraints for their farm. The concepts explored in this analysis, which combined experimental data, computer simulation, and long-term weather data to generate optimum management recommendations, could be applied in other areas with constrained water supplies for irrigation. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Kisekka, I., Aguilar, J. P., Rogers, D. H., Holman, J., O'Brien, D. M., & Klocke, N. (2016). Assessing deficit irrigation strategies for corn using simulation. Transactions of the Asabe, 59(1), 303-317. doi:10.13031/trans.59.11206
Keywords: Corn; Crop Modeling; Deficit Irrigation; Water Limited; Water Productivity; Aquifers